The Effect of Return on Equity and Current Ratio on Price to Book Value (Case Study of PT Unilever Indonesia Tbk which is Listed on the Indonesia Stock Exchange for the 2015-2022 Period) - Siti Maesaroh; Raden Rijanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to find out how Price to Book Value is influenced by Return on Equity and Current Ratio. The focus of the research is PT Unilever Indonesia Tbk, which is listed on the Indonesia Stock Exchange. The sample for this research is the financial statements of PT Unilever Indonesia Tbk from 2015 to 2022. An impossible sample selection method was used. Instead, data analysis is carried out using several techniques. This includes classical assumption tests, correlation tests, multiple linear regression coefficient of determination tests, and partial and simultaneous hypothesis tests. The research results show that Return on Equity (X1) and Current Ratio (X2) do not partially influence Price to Book Value. Apart from that, Return on Equity does not partially affect Price to Book Value (Y) significantly at all